Chronic deficit in the expression of voltage-gated potassium channel Kv3.4 subunit in the hippocampus of pilocarpine-treated epileptic rats - Pacheco Otalora, Luis F. (2010)
Voltage gated K(+) channels (Kv) are a highly diverse group of channels critical in determining neuronal excitability. Deficits of Kv channel subunit expression and function have been implicated in the pathogenesis of epilepsy. In this study, we investigate whether the expression of the specific subunit Kv3.4 is affected during epileptogenesis following pilocarpine-induced status epilepticus. For this purpose, we used immunohistochemistry, Western blotting assays and comparative analysis of gene expression using TaqMan-based probes and delta-delta cycle threshold (Δ ΔCT) method of quantitative real-time polymerase chain reaction (qPCR) technique in samples obtained from age-matched control and epileptic rats. A marked down-regulation of Kv3.4 immunoreactivity was detected in the stratum lucidum and hilus of dentate gyrus in areas corresponding to the mossy fiber system of chronically epileptic rats. Correspondingly, a 20% reduction of Kv3.4 protein levels was detected in the hippocampus of chronic epileptic rats. Real-time quantitative PCR analysis of gene expression revealed that a significant 33% reduction of transcripts for Kv3.4 (gene Kcnc4) occurred after 1 month of pilocarpine-induced status epilepticus and persisted during the chronic phase of the model. These data indicate a reduced expression of Kv3.4 channels at protein and transcript levels in the epileptic hippocampus. Down-regulation of Kv3.4 in mossy fibers may contribute to enhanced presynaptic excitability leading to recurrent seizures in the pilocarpine model of temporal lobe epilepsy.